Integrated on-chip mass spectrometry reaction monitoring in microfluidic devices containing porous polymer monolithic columns. Issue 18 (4th July 2016) - Dietze, C.; Schulze, S.; Ohla, S.; Gilmore, K.; Seeberger, P. H.; Belder, D.
Abstract : Seamless combination of chemical reactions, electrochromatographic separation and electrospray ionization in one single microfluidic device. Abstract : Chip-based microfluidics enable the seamless integration of different functions into single devices. Here, we present microfluidic chips containing porous polymer monolithic columns as a means to facilitate chemical transformations as well as both downstream chromatographic separation and mass spectrometric analysis. Rapid liquid phase lithography prototyping creates the multifunctional device economically.